Analisis Framing Pemberitaan Tindak Dan Upaya Bunuh Diri di tribunnews.com - Ratih Latifah Murniati; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Suicidal behavior is still considered taboo to discuss, plus victims or survivors of suicide are still vulnerable to the negative stigma that society has pinned on them. This stigma can be formed or strengthened by reporting by the media as a source of information. The reporting of suicide acts and attempts can also trigger copycat suicide for vulnerable groups if not done carefully. Tribunnews.com sees suicide reporting as an important issue to raise, but it also needs to be seen from the quality of the news produced, the suitability and sensitivity of journalists to the ethics of reporting on suicide. So this study aims to determine the frame of Tribunnews.com and from the frame that appears in this study, ethical violations are identified in reporting on suicide acts and attempts. A total of 15 news items in the November 2019 - January 2020 period were selected based on 3 dominant narratives analyzed using framing analysis with the Zhongdang Pan and Kosicki models. This framing device consists of four elements, namely syntactic structure, script structure, thematic structure, and rhetorical structure. The theories used in this research are Social Responsibility Theory and ethical guidelines for reporting on suicide. The results showed that there were 8 news frames conducted by Tribunnews.com on suicide victims, namely (1) people with depression or mental disorders, (2) people who behave strangely, awkwardly, aggressively, and act suddenly, (3) a person a rule breaker, dangerous, and close to the crime, (4) lack of consideration and narrow-mindedness, (5) someone who has bad social relationships and a disharmonious family, (6) someone who is closed, quiet, gloomy, tends to be problematic, ( 7) weak, (8) and always determined to die. Ethically, points that are often violated are points 1, 4, 9, and 14 of the Press Council's Guidelines for Reporting Regarding Suicide Acts and Attempts. Then it violates points 2, 9, and 10 in the guidelines from the World Health Organization (WHO). The violation shows that the news is sensationally packaged, spreads myths about suicide, contains stigma against victims, and is too detailed in explaining the suicide incident.